Appunti da e per un seminario. Tra progetto d’infrastruttura e progetto urbano: il caso della tramvia di Firenze - Alberti, Francesco (Ri-Vista. Research for landscape architecture, 2015)
For twenty years we have observed all over Europe a renaissance of the tramway as a public transport system. This phenomenon can be related to the upgrades of technology and especially to the interventions of urban improvement usally carried out together with the construction of new tracks. On the contrary, in Florence, where a new tram network has been building since 2004, a traditional sectorial approach has still prevailed, unable to offer solutions to conflicting uses of the street space. Consequently citizens’ hostility against the tramway has increased. The University of Florence has attempted to reopen the discussion about the positive link between new infrastructures and urban renovation, promoting a seminar, that has been joined by town planners, transport experts, politicians and public officials. As a contribute, there was presented a proposal –both methodological and effective- in order to align the Florentine project to the quality standards achieved in other european cities.